(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Mining is accompanied by direct irreversible changes in the biosphere. Analysing the results of recent studies on the anthropogenic hazard of coal mine tailings and the peculiarities of tailings reclamation and phytoremediation on a global scale, it necessitates the investigation of the ecological state and natural phytoremediation of the Nadiya mine tailings in the Lviv-Volyn coal basin. The stages of succession processes on the rock dump surface have been determined. The phytomeliorative efficiency coefficient has been calculated for all periods of the phytomeliorative process on the rock dump surface. The total area of the studied site is 280 m2. Based on the calculations of changes in the dynamics of the phytomeliorative efficiency coefficients at different stages of the phytomeliorative process (KFM=0.155-4.485), it is expedient to conduct reclamation and phytomeliorative operations on the rock dump surface. The coal mining industry causes a significant technogenic burden on the environment, affects human health and transforms living conditions regardless of the place or country of extraction. Waste heaps are the most dangerous factors of environmental degradation. Studies of the impact of coal mine waste heaps on the human body and biota are conducted in almost all industrialised countries as well as countries where mineral mines are operated.